Cortisol Levels in Infants with Central Coordination Disorders during Vojta Therapy - Wojciech Kiebzak; Arkadiusz Żurawski; Stanisław Głuszek; Michał Kosztołowicz; Wioletta Adamus Białek (MDPI AG, 2021)
Background: Due to the decrease in the percentage of perinatal mortality, which is one of the Millennium Development Goals, the number of children with a central coordination disorder (CCD) has increased, present in up to 40% of premature babies. Neurodevelopmental disorders detected in the diagnostic process require early interventions that will eliminate or overcome existing dysfunctions. These treatments often cause discomfort in the infant, which induces insecurity and activation of basic defense mechanisms. The aim of the work is to assess changes in cortisol concentration in infants treated with the Vojta method. Methods and findings: The study included 35 children with CCD aged between three and nine months. The participants had no comorbidities that could have affected the obtained results. The activities were planned to occur in three stages: 1. Collection of a saliva sample directly before the physiotherapy appointment. 2. Collection of saliva immediately after rehabilitation. 3. Collection of saliva 20 min after the end of rehabilitation. The physiotherapeutic intervention included the assessment of seven reactions of the body position in space according to Vojta and the conduct of a therapeutic session consisting of the first phase of rotation and creeping reflex according to Vojta. The concentration of free cortisol in saliva was assessed with LC-MS/MS. In the first measurement, none of the children presented an excess of the normative concentration of cortisol. The cortisol measurement performed directly after rehabilitation showed above-normative values in three children. In the third measurement, all of the children presented a decreased concentration of free cortisol. The analysis (paired two-tailed t-test, p < 0.05) showed statistically significant differences between particular stages of the measurements. The analysis of the scores obtained in the second measurement showed the concentration of scores in the area of "normal" at a level of 0.83 (normal concentration) and the area "above normal" at the level of 0.005 (very weak concentration). Based on the analysis of significance of the obtained scores, it was found that the result was not accidental, and the Vojta method used in the treatment of children with CCD was suitable. Conclusions: Here, for the first time, we presented how Vojta therapy was correlated with cortisol levels among children with a central coordination disorder.